Light microscopy and ultrastructure of the liver of Astyanax altiparanae Garutti and Britski, 2000 (Teleostei, Characidae) - Bertolucci, Bruno [UNESP]; Vicentini, Carlos Alberto [UNESP]; Vicentini, Irene Bastos Franceschini [UNESP]; Bombonato, Maria Terezinha Siqueira [UNESP] (My University, 2008)
Livers of thirty specimens of Astyanax altiparanae obtained from a commercial fish farm were subjected to light and transmission electron microscopy, in order to describe the hepatic parenchyma and the intrahepatic exocrine pancreatic tissue. Anatomically, the liver showed only three hepatic lobes. Histological analysis demonstrated that the hepatocytes were spread out as anastomotic cords, arranged in two cellular layers and surrounded by sinusoids. The intrahepatic exocrine pancreatic tissue exhibited an acinar arrangement and was diffused in the hepatic parenchyma. Ultrastructural analysis showed that the hepatocytes had a rounded nucleus and a rough endoplasmatic reticulum, with a parallel disposition to the nuclear membrane. The exocrine pancreatic cells showed secretion granules at the apical portion, and the rough endosplasmatic reticulum was concentrically distributed.
Keywords: Exocrine pancreas; Hepatocyte ultrastructure; Liver histology; Teleost